The Role of Transesophageal Echocardiography in Adolescents and Adults with Congenital Heart Disease - Sheikh, Naveen; Banerjee, Sajal Krishna; Rahman, Fazlur; Hossen, Zahid; Ahmed, CM; Haque, Harisul; Habib, SMA; Noornabi, Md; Muqueet, MA; Khondaker, -; Hossain, Nizamul; Hasan, ATM Iqbal; et al. (University Heart Journal, 2017)
There is frequent dropout of atrial septal echoesin the region of the fossa ovalis in the standard precordial echocardiographic imaging planes, that can be minimized by use of the subcostal imaging approach. The diagnostic sensitivity of this approach was reviewed in 154 patients (mean age 31 years, range 18years to 45 yrs) with documented atrial septal defect in whom a satisfactory image of the atrial septum could be obtained.Subcostal two-dimensional and color Doppler echocardiography successfully visualized 93 (89%) of the 105 ostium secundum atrial septal defects, all 32 (100%) ostium Primum defects and 7 (44%) of the 16 sinus vinosus defects. A defect was not visualized (false negative response) in 12 patients (11 %) with an ostium secundum defect and in 9 patients (56%) with a sinus venosus defect. In three of the former and five of the latter, a two-dimensional echocardiographic contrast examination and transesophageal echocardiography established the presence of the inter-atrial shunt. Forty eight patients (32 %) with clinical findings of uncomplicated atrial septal defect confirmed by two-dimensional,color Doppler and Transesophageal echocardiography underwent surgical repair of the defect without preoperative cardiac catheterization. There were no perioperative complications. University Heart Journal Vol. 11, No. 2, July 2015; 63-67